Community Perspectives, Language Ideologies, and Learner Motivation in Chickasaw Language Programs - Ozbolt, Ivan (My University, 2014)
This study examines language ideologies in the Chickasaw Nation of Oklahoma, in the context of various efforts to revitalize this Muskogean language. There are approximately sixty-five remaining first language speakers out of a total population of about 57,000 tribal citizens. I analyze the underlying discourses in the community about the importance of preserving the language. I argue that these discourses are part of a broader project of nation-building meant to foster tribal citizens’ sense of identity, while demonstrating the relevance of the Chickasaw Nation to the state of Oklahoma and to the United States. These discourses justify the necessity of language revitalization to the Chickasaw community and to the larger society. This study examines people’s responses to these initiatives and discourses, and their general understanding, views, and aspirations regarding language revitalization. In particular, I examine their motivation to learn Chickasaw and the challenges of motivating other people to become learners. I argue that positive attitudes towards a language and access to resources do not automatically translate into action to learn it. I also review people’s views on bilingualism in English and Chickasaw, and their attitudes towards schools and homes as sites of language revitalization. I conclude that boosting people’s positive attitudes towards an endangered language is an important first step towards language revitalization, but that much remains to be done in terms of producing conversationally proficient second language speakers to recreate a speech community.
Keywords: Language ideologies, language loss and revitalization, Chickasaw Nation of Oklahoma, learner motivation